Jumping Characteristics of Broiler Breeder Hens at Different Perching Platform Heights - Xiaoliu Xue; Baoming Li; Qin Tong; Yang Wang; Peng Yin (Animals)
Excessive mating is a significant welfare concern for floor-reared broiler breeder hens. Perches have shown potential as a solution to mitigate this issue; however, limited research is available on the design parameters of perches. Understanding the jumping characteristics of broiler breeder hens is crucial for designing safe and functional perches. In this study, perching platforms were selected to ensure the safety of hens during jumps. Videos of hens performing voluntary jumps from varying heights (35, 40, 45, and 50 cm) were analyzed using Tracker (version 6.2.0) software. The results showed that the take-off latency (TL) and jump duration (JD) increased with height increases, with downward jumps exhibiting a 66.1% and 10.7% higher TL and JD than those of upward jumps (based on mean values), respectively. However, the latency to achieve balance (LAB) decreased by 76.5% during downward jumps (based on mean values). During upward jumps, both the wing-beating frequencies during the jump (WBJD) and after landing (WBL) increased with height increases. The interaction between the height and direction of jumping significantly affected the horizontal displacement (body) and angles (body and head) during the JL phase (p < 0.05). The body horizontal displacement during downward jumps was up to 70.3% higher than that during upward jumps (based on mean values), while the downward body angles were more minor than those during upward jumps. The lowest body and head angles of downward jumps were 42.2° ± 5.4° and 33.4° ± 5.6°, respectively. The results related to TL and LAB are expected to provide guidance for designing appropriate heights in perching facilities. Meanwhile, the findings on horizontal displacement and jump angles offer valuable insights for the safe distance and angle design between perching platforms.